2014
DOI: 10.1371/journal.pone.0102943
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Antismoking Television Advertisements on Cessation by Race/Ethnicity, Socioeconomic Status, and Mental Health Status

Abstract: Disparities in tobacco use and smoking cessation by race/ethnicity, education, income, and mental health status remain despite recent successes in reducing tobacco use. It is unclear to what extent media campaigns promote cessation within these population groups. This study aims to (1) assess whether exposure to antitobacco advertising is associated with making a quit attempt within a number of population subgroups, and (2) determine whether advertisement type differentialy affects cessation behavior across su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…This study also provides further support for previous research showing that hard-hitting, general population antismoking media campaigns can be used to promote quit attempts across a variety of demographic subpopulations (McAfee et al, 2013(McAfee et al, , 2015Nonnemaker et al, 2014). Specifically, we found patterns in PE varied by race/ethnicity and mental health status, indicating that vulnerable populations report higher PE scores.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study also provides further support for previous research showing that hard-hitting, general population antismoking media campaigns can be used to promote quit attempts across a variety of demographic subpopulations (McAfee et al, 2013(McAfee et al, , 2015Nonnemaker et al, 2014). Specifically, we found patterns in PE varied by race/ethnicity and mental health status, indicating that vulnerable populations report higher PE scores.…”
Section: Discussionsupporting
confidence: 87%
“…Previous research suggests that antismoking campaigns that target all smokers with "why to quit" messages may be equally or more effective among ethnic/racial minorities (Davis et al, 2011a;Durkin, Biener, & Wakefield, 2009;McAfee, Davis, Alexander, Pechacek, & Bunnell, 2013Nonnemaker et al, 2014). More recent evidence (McAfee et al, 2013(McAfee et al, , 2015 has shown that the Tips campaign likely had the greatest effects on quit attempts among non-Hispanic black smokers despite the campaign including an ethnically diverse group of ad participants.…”
Section: Introductionmentioning
confidence: 99%
“…Of the studies that do include smokers from diverse racial/ethnic backgrounds, most do not include adequate representation from Asian Americans, Pacific Islanders, American Indians/Native Alaskans, Native Hawaiians [e.g., 10,29,32,41] or multiracial smokers [e.g., 10,29,32,33,41]. Moreover, consideration of race/ethnic differences including these groups is lacking [e.g., 30,42].…”
Section: Discussionmentioning
confidence: 99%
“…Five studies investigated racial/ethnic differences in quit attempts using survey methods. In a random-digit-dial telephone survey of Whites, African Americans, and Hispanics, Nonnemaker et al [32] found that potential antismoking advertisement exposure (measured by television gross rating points) was positively associated with quit attempts in Whites and Hispanics. Confirmed advertisement recall was positively related to quit attempts among Whites and African Americans, with the highest odds of making a quit attempt associated with emotional or graphic images.…”
Section: Correlates Of Cessation-related Cognitions and Behaviorsmentioning
confidence: 99%
“…Disparities in tobacco use among adults continue to exist by race/ethnicity, education, income, and mental health status. 6 In the last decade, smoking prevalence has declined in all age groups in the US except for older smokers. In fact, smoking prevalence for adults over 65 actually has increased.…”
Section: Prevalence and Impact Of Smoking In Older Adultsmentioning
confidence: 99%